Separation of Electronic and Steric Effects: Oxidation of ortho-substituted N,α-Diphenylnitrones by Pyridinium Fluorochromate in Aqueous DMF Medium - Gopalkrishanan, M.; Jayabharthi, J.; Thanikachalam, V. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of some ortho-substituted N,α-diphenyl-nitrones with pyridinium fluorochromate (PFC) in aqueous DMF medium have been investigated. The rate equation ν = k[nitrone][oxidant] is found to be valid. Regression analyses of the rate data by using Taft and Charton equation to separate steric effect from electronic effects have been carried out. Results indicate that the steric effect plays a major role while localized and resonance effects playa minor role.